Time to death and health expenditure of the Czech health care system - Kateřina Pavloková (Charles University in Prague, Institute of Economic Studies (IES), 2009)
Growing concern about future sustainability of public budgets in the context of population ageing has given rise to a large debate on the role of age in the context of health care expenditure. Growing evidence on the so called death related costs hypothesis arguing that the positive relationship between age of the cohort and related health care expenditure is the result of growing probability of death changes in an important manner the results of the projections. The aim of this paper is to explore the importance of the death related costs hypothesis in the Czech health expenditure data and the impact of the hypothesis on the projection of the financial sustainability of the Czech health care system.
Keywords: H51; 330; health care; last year of life; financial sustainability; Gesundheitswesen; Gesundheitskosten; Alternde Bevölkerung; Sterblichkeit; Tschechische Republik